Promising polymeric compounds for coronary stent graft membrane - M. A. Rezvova; E. A. Ovcharenko; K. Yu. Klyshnikov; Yu. A. Kudryavtseva (Кардиоваскулярная терапия и профилактика)
The literature review discusses the studies on developing the polymer membrane of a coronary stent graft. The new generation of coronary stent grafts is designed to increase the hemocompatibility and ensure its delivery to poorly accessible artery regions. Based on the clinical use results, three groups of promising polymers were identified: biostable polyurethanes, polyvinyl alcohol-based cryogels, bioresorbable compositions based on polylactide-caprolactone and lactic acid-glycolic acid copolymer. However, the possibility of their clinical application requires further experimental studying.